Background: Prolonged post-anesthesia care unit (PACU) stay is a critical indicator of postoperative efficiency and hospital resource utilization. Delayed recovery may compromise patient flow, increase the risk of complications, and strain perioperative s - Noprianty, Richa; Anjelita, Tia; Mustopa, Ahmad; Wahyudi, Fikri Mourly (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2021)
Background: Prolonged Post-Anesthesia Care Unit (PACU) stay represents a critical indicator of postoperative care efficiency and resource utilization. Extended PACU duration can lead to patient accumulation, increased complication risks, and healthcare system strain.Objective: To identify and analyze risk factors associated with prolonged PACU stay following general anesthesia, with particular emphasis on surgery type as a dominant predictor.Methods: A cross-sectional observational study was conducted using modified data from 96 patients undergoing general anesthesia. Data collection included patient demographics, ASA physical status, pain scores, surgical duration, comorbidities, surgery type, anesthesia technique, and patient transfer timing. Statistical analysis employed chi-square tests and logistic regression to identify significant predictors of prolonged PACU stay (≥30 minutes).Result: Among 96 patients, 37.5% experienced prolonged PACU stay (≥30 minutes). Significant predictors included age (p=0.011), ASA physical status (p=0.012), anesthesia technique (p=0.035), and surgery type (p=0.001). Multivariate logistic regression identified surgery type as the dominant factor (p=0.004, OR=2.524, 95% CI: 1.355-4.700). Major surgeries demonstrated 60% prolonged stay rates compared to 21.8% for minor procedures. Pain intensity, surgical duration, comorbidities, and patient pickup time showed no significant association.Conclusion: Surgery type emerges as the primary determinant of prolonged PACU stay, with major surgical procedures significantly increasing recovery duration. These findings provide evidence-based guidance for perioperative planning, resource allocation, and quality improvement initiatives in postoperative care.